Effect of agrochemicals on macroinvertebrate assemblages in Pampasic streams, Buenos Aires, Argentina - Solís, Marina Laura (2017)
Agricultural practices have been intensified in recent decades in Argentina. The Pampa plain is the main agricultural region of the country. The effect of increased application of agrochemicals on the invertebrate fauna of the Pampasic streams remains unreported. In the present study, we compared the abundance and composition of invertebrate assemblages in seven Pampasic streams with contrasting soil use in their basins. Two streams run through intensively cropped plots, two drain basins with livestock fields, while the other three are located within a biosphere Reserve. Higher nutrient and insecticide concentrations were measured in the streams draining cropped basins, related with pesticide applications and crop fertilization. The invertebrate assemblage composition of the cropped streams differed significantly from the others and between the two. Present evidence suggests that the impact of agrochemicals results in a change in composition with decreased abundance or absence of sensitive species such as Hyalellidae, Caenidae, Baetidae and Curculionidae and increased abundance of more tolerant taxa: Ostracoda, Glossiphoniidae (Hirudinea), Ancylidae (Gundlanchia), Ampullariidae (Pomacea canaliculata), Sphaeriidae and Dugesiidae. Available information suggests that macrophyte cover and composition also influence the invertebrate assemblages of the Pampasic streams.